2010
DOI: 10.1074/jbc.m110.146589
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Protein Kinase A Localization Using a Trans-activator of Transcription (TAT)-conjugated A-kinase-anchoring Peptide Reduces Cardiac Function

Abstract: Localization of protein kinase A (PKA) via A-kinase-anchoring proteins (AKAPs) is important for cAMP responsiveness in many cellular systems, and evidence suggests that AKAPs play an important role in cardiac signaling. To test the importance of AKAP-mediated targeting of PKA on cardiac function, we designed a cell-permeable peptide, which we termed trans-activator of transcription (TAT)-AKAD for TAT-conjugated A-kinase-anchoring disruptor, using the PKA binding region of AKAP10 and tested the effects of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…In line with these findings, treatment of Langendorff-perfused mouse hearts with transactivator of transcription-conjugated anchoring disruptor peptides containing the PKA-binding region of AKAP10 strongly reduced the phosphorylation of cardiac PKA substrates, heart rate, and left ventricular developed pressure in response to isoproterenol stimulation (88). Collectively, these findings provide solid evidence for the importance of AKAPs in the compartmentalization of PKA and the regulation of cardiac function.…”
Section: Pka Anchoring In the Heartsupporting
confidence: 73%
See 1 more Smart Citation
“…In line with these findings, treatment of Langendorff-perfused mouse hearts with transactivator of transcription-conjugated anchoring disruptor peptides containing the PKA-binding region of AKAP10 strongly reduced the phosphorylation of cardiac PKA substrates, heart rate, and left ventricular developed pressure in response to isoproterenol stimulation (88). Collectively, these findings provide solid evidence for the importance of AKAPs in the compartmentalization of PKA and the regulation of cardiac function.…”
Section: Pka Anchoring In the Heartsupporting
confidence: 73%
“…Several studies have shown that the disruption of PKA anchoring in cardiomyocytes and in intact hearts inhibits PKAmediated phosphorylation of cTnI and cMyBP-C (15,26,75,88). Although these results demonstrated that cTnI and cMyBP-C phosphorylation requires AKAP-mediated PKA anchoring, the identity of the AKAP(s) mediating this function is still unknown.…”
Section: Akaps and Myofiber Contractilitymentioning
confidence: 51%
“…Studies over the past decade have illuminated our understanding of their non-redundant biological role, usually through sequestering each PKA type to distinct intracellular signaling compartments. Recent studies employing various imaging techniques show overlapping staining patterns at the cardiac sarcomere for both PKA-RI and PKA-RII (11,45). The striated staining is largely abolished in the presence of peptide disruptors.…”
Section: Discussionmentioning
confidence: 99%
“…Cellpermeable peptides that displace PKA from AKAPs have helped delineate AKAP function in Tcells [105], pancreatic b cells [106], adrenocortical cells [105], cardiac myocytes [107,108], hippocampal neurons [109] and renal principal cells (reviewed in [110]). …”
mentioning
confidence: 99%